Analisis Ketidaklayakan Upah Pekerja Formal Perempuan Nonpemerintah di Provinsi Jawa Timur Tahun 2023 - Salsabila, Syarifa; Sitorus, Jeffry Raja Hamonangan (Politeknik Statistika STIS, 2025)
Workers must receive decent wages to meet living needs. Formal female workers have employment protection, but their wages are still inadequate, especially in non-government sector. East Java contributes greatly to national economy with high percentage of women working, but their wages are relatively low. This study aims to determine the description of inadequate wages also identify the influence and tendencies of individual and city variables on the inadequate wages of formal non-government female workers in East Java using Sakernas August 2023 and BPS publication. The results of multilevel binary logistic regression show that at the individual level, education level, certified training participation, work experience, and union participation, also female Human Development Index as variable at the city level, significantly affect the inadequate wages of formal non-government female workers in East Java. Attention should be on education, skill development, experience, union, and live quality in working area to overcome the problem.